PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN DAN WORD OF MOUTH MAHASISWA PROGRAM STUDI DIPLOMA III ADMINISTRASI PERPAJAKAN FISIP USU - Aida W Batubara (Universitas Muhammadiyah Sumatera Utara, 2017)
The objective of the research was to know and to analyze the influence of service quality on students’ word of mouth through their satisfaction in the Diploma III of Taxation Administration Study Program, FISIP USU. The type of the research was descriptive quantitative and its nature was descriptive explanatory. The result of the research showed that 1) service quality had positive and significant influence on students’ word of mouth through their satisfaction, 2) satisfaction had positive and significant influence on students’ word of mouth, and 3) there was indirect influence of service quality on students’ word of mouth through their satisfaction with the value of 0.235, while there was direct influence of service quality on students’ word of mouth with the value of 0.394 which indicated that direct influence was more dominant that indirect influence.